Tips and Tricks in Contrast-Enhanced Ultrasound (CEUS) for the Characterization and Detection of Liver Malignancies - Schellhaas, Barbara; Strobel, Deike (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Contrast-enhanced ultrasound (CEUS) has a high diagnostic accuracy in the assessment of focal liver lesions. Clinical context (presence of liver cirrhosis, history of other malignancy versus incidental finding) is crucial for the correct interpretation of CEUS findings. CEUS has to be preceded by structured anamnesis and clinical examination as well as accurate B-mode sonography. Metastases are the most common malignant liver lesions in a non-cirrhotic liver. According to their contrast enhancement in the arterial phase, metastases are categorized as hyper- and hypo-vascular metastases. A common feature of all metastatic lesions is washout of the contrast agent in the portal venous or late phase. In the context of liver cirrhosis, > 95 % of focal liver lesions are hepatocellular carcinomas (HCCs). HCCs typically show arterial phase hyperenhancement, followed by mild and gradual contrast washout occurring very late in the late phase. For intrahepatic cholangiocellular carcinoma (ICC), the pattern of contrast enhancement in the arterial phase can vary. However, all ICCs typically show early and pronounced washout. Other liver malignancies like lymphoma, angiosarcoma, epithelioid hemangioendothelioma and others are very rare. Except for the contrast washout seen in all liver malignancies, they do not display pathognomonic enhancement patterns upon CEUS. Thus, biopsy is indispensable for definite diagnosis of the tumor entity. Furthermore, CEUS is used for the detection of metastases and therapeutic monitoring after local ablative procedures. The examination procedure differs slightly depending on the specific indication (characterization, detection).Die Kontrastmittelsonografie (CEUS, contrast enhanced ultrasound) hat eine hohe diagnostische Genauigkeit in der Dignitätsbeurteilung fokaler Leberläsionen. Der klinische Kontext (zirrhotische versus nicht zirrhotische Leber, maligne Grunderkrankung versus Zufallsbefund) ist entscheidend für die differenzialdiagnostische Einordnung von Leberraumforderungen. In jedem Fall muss der Kontrastmittelsonografie eine eingehende Anamnese und sorgfältige B-Bild-Sonografie der gesamten Leber vorangehen. Die häufigsten malignen Leberläsionen in nicht zirrhotischer Leber sind Metastasen, die nach ihrer Kontrastmittelaufnahme in der arteriellen Phase unterschieden werden in hyper- und hypovaskularisierte Metastasen. Allen Metastasen gemeinsam ist ein Kontrastmittelauswaschen in der portalvenösen Phase oder Spätphase. In zirrhotischer Leber sind > 95 % der soliden Läsionen hepatozelluläre Karzinome (HCCs). HCCs zeigen typischerweise ein arterielles Hyperenhancement und ein mildes, sehr spätes Kontrastmittelauswaschen in der Spätphase. Intrahepatische cholangiozelluläre Karzinome (ICCs) zeigen in der arteriellen Phase ein variables Kontrastmittel-Enhancement und in der Regel ein sehr frühes und stark ausgeprägtes Kontrastmittelauswaschen. Andere Lebermalignome (wie z. B. Lymphome, Angiosarkome, epitheloide Hämangioendotheliome etc.) sind Raritäten. Mit Ausnahme des für alle Lebermalignome charakteristischen Kontrastmittelauswaschens zeigen diese Raritäten kein pathognomonisches Kontrastierungsmuster; zur Bestimmung der Tumorentität ist eine Biopsie erforderlich. Weitere Einsatzgebiete der Kontrastmittelsonografie sind die Metastasen-Detektion sowie die Erfolgskontrolle nach lokalablativen Verfahren. Der Untersuchungsablauf in der Kontrastmittelsonografie unterscheidet sich je nach Indikation (Charakterisierung, Detektion).